World team - Vyner, Tim. (Brookfield, CT : Roaring Brook Press, 2002)
All over the world, children in places as different as Germany, Kenya, Japan, Australia, and India are practicing and playing soccer, all dreaming of winning the World Cup.
Accelerated Reader AR
Keywords: Soccer -- Fiction